Investment Strategies In The Indian Stock Market: A Survey - Tripathi, Vanita (Indian Journal of Finance, 2009)
This paper examines the perceptions, preferences and various investment strategies in Indian stock market on the basis of a survey among 93 investment analysts, fund managers and active equity investors during March-October 2007. Survey findings reveal that investors use both fundamental as well as technical analysis while investing in Indian stock market. Most of the respondents strongly agree that various company fundamentals ( such as size, book to market equity, price earnings ratio, leverage etc.) significantly influence stock prices and hence addition of these factors in asset pricing model can better explain cross sectional variations in equity returns in India. Five most widely used investment strategies in Indian equity market are size based strategies, momentum strategies, following FIIs investment behaviour, buying stocks on the basis of 30 days moving average and buying stocks on the basis of relative strength index. There has been a substantial change in investment strategies used by active investors in Indian stock market over the past five years with a shift from purely technical analysis based strategies to the one which involves both fundamental and technical analysis. The investment horizon of investors has also reduced due to higher volatility. These findings are important in understanding the behaviour of investors in Indian stock market and bring new insights into issues such as asset pricing, market efficiency and investment strategies.